Towards Cooling Tower Efficiency-An Energy Audit Approach - Alwin, Long Su Weng; Atnaw, Samson M.; Roziah, Zailan; Muhamad Muhtazam, Noor Din (EDP Sciences, 2017)
This research studied the power generation trends from national grid and gas for a period of 4 years. Energy audit of critical systems like this is needful for optimal energy utilization. An energy audit was carried outon 6 industrial cooloing towers and their annual operating cost calculated. Variable speed drive suggested was installed and corresponding annual energy savings of 114,900 kWh/year cost saving of RM30,000 was achieved at a case study plant located in Malaysia. Cooling towers with smart systems was recommended for higher energy savings.